Care haunts, hurts, heals: The promiscuous poetics of queer crip Mad care. Issue 3 (21st May 2021) - Eales, Lindsay; Peers, Danielle
Abstract: Care is a dirty word for many in our communities. "Caregiving" has become a euphemism for often-indifferent, under-funded labor that is done to our bodies to (barely) enable our continued survival. Care is a dirty word in many of our leftist-feminist communities. Care work is a classification of highly gendered and racialized labor that remains largely unpaid, underpaid, and deeply devalued. Care is a dirty word in our Mad, disability, queer activist communities. "Taken into care" often refers to indefinite confinement, forced extraction from communities and families, and the removal of one's right to self-determination. Is care even worth reclaiming? In this creative duo-ethnography, a Mad fat femme and a crip ill non-binary queerdo wander through various moments when care has most impacted our lives, our relationships, and our communities. We have each held one another with care on the precipice of dying. Our bodies have shouldered the love-labor of care in the most intimate, exigent, and banal of moments: consensual and playful medication reminders, postsurgery tampon changing, literally squeezing out another's breath to stay alive—and then repeating—hundreds of times an evening. We have also experienced care that was much too careful, and anything but full of care. We have shared care promiscuously with our crip and Mad (arts) communities in ways that have been life affirming, life changing, sometimes life making, other times life threatening. Through this wandering with ideas, moments, and communities, we reflect upon multiple dimensions of Mad, queer, crip care. Whom is the caring for? What is our care about? And how can our care be given or giving, taken or shared, offered, enabled, and co-created with flourish?